(untitled) (Eurasian Journal of Engineering and Technology, 2022)
The article scientifically analyzes the role of the community in increasing the social activity of young people. In teaching young people about vital issues, such as independent organization of their activities, self-government, worldview, it is important that they strive for self-improvement.